The Evaluation of the Implementation of the Independent Curriculum E-Report at Ngasinan Elementary School, Semarang Regency - Murtiari Setyaningtyas; Yari Dwikurnaningsih; Bambang Ismanto (Jurnal Indonesia Sosial Sains, 2024)
To facilitate teachers in administrative matters related to reporting students' learning outcomes, an E-Report is used as a reporting tool. This research aimed to analyze or evaluate the use of the Independent Curriculum E-Report at Ngasinan Elementary School in Semarang Regency. The research utilized the CIPP evaluation model (Context, Input, Process, Product). Interviews, documentary studies, and observations were employed to collect data. Data collection, data reduction, data presentation, and drawing conclusions were the data analysis techniques used in this research. The research findings on the contextual aspect align with the Curriculum Implementation Guidelines, which emphasize the periodic delivery of student reports through E-Reports. The input aspect in the areas of planning, human resources, financing, and infrastructure is generally in accordance, but there is a need for improvement in certain areas. The process aspect includes pre-implementation procedures, implementation, management of infrastructure, human resources, and financing in accordance with the guidelines. The product aspect involves the improvement of human resource quality, accurate and up-to-date information, accountability, efficiency, convenience, and reports in both print and digital formats. The driving factors include collaboration, awareness, convenience, motivation, transparency, infrastructure, financing, and efficiency. The inhibiting factors include a lack of infrastructure, internet connectivity, skills, and systems.